Zad.

Doprowadź do najprostszej postaci:

a) ( 8x – 2y) + ( 2x - 8) +20 =



b) (2x - 3) + ( 5x - 5) - ( 2x - 9)=



c) 6( 2a+5b-2) =



d) -5(-x+3y-4) =



e) 4( 2a + b) – 3( 3a + 6b – 1 ) +3 a =



f) 2( 7x + 2y) - 4( 3x - 8y) +3(2x - 4 ) =



Odpowiedź :

Odpowiedź:

a)8x-2y+2x-8+20=10x-2y+12

b)2x-3+5x-5-2x+9=5x+1

c)12a+30b-12

d)5x-15y+20

e)8a+4b-9a-18b+3+3a=2a-14b+3

Szczegółowe wyjaśnienie:

a) (8x – 2y) + (2x - 8) + 20 = 8x - 2y + 2x - 8 + 20 = 10x - 2y + 12

b) (2x - 3) + (5x - 5) - (2x - 9) = 2x - 3 + 5x - 5 - 2x + 9 = 5x + 1

c) 6(2a+5b-2) = 12a + 30b - 12

d) -5(-x+3y-4) = 5x - 15y + 20

e) 4(2a + b) – 3(3a + 6b – 1 ) + 3a = 8a + 4b - 9a - 18b + 3 + 3a = 2a - 14b + 3

f) 2(7x + 2y) - 4(3x - 8y) + 3(2x - 4 ) = 14x + 4y - 12x + 32y + 6x - 12 = 8x + 36y - 12

Mam nadzieję że pomogłam i liczę na naj. ♥

Inne Pytanie